2019
DOI: 10.2519/jospt.2019.8190
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Passing Return-to-Sport Criteria and Second Anterior Cruciate Ligament Injury Risk: A Systematic Review With Meta-analysis

Abstract: Background There is no consensus on the components of return-to-sport (RTS) testing following anterior cruciate ligament (ACL) reconstruction or whether passing RTS criteria can reduce a patient's risk of reinjury. Objectives To determine whether impartial, criteria-based RTS decisions are associated with less risk of a second ACL injury (either graft failure or contralateral ACL injury). Methods In this systematic review with meta-analysis, the authors conducted an electronic literature search in PubMed/MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
136
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 77 publications
6
136
1
2
Order By: Relevance
“…Criteria for when to let the athletes progress are not standardised and experts disagree on the choice of follow-up patient-reported and physical performance-based outcome measures 19 20. There is no agreement on the key criteria that should be met before return to sport 11 21–23…”
Section: Introductionmentioning
confidence: 99%
“…Criteria for when to let the athletes progress are not standardised and experts disagree on the choice of follow-up patient-reported and physical performance-based outcome measures 19 20. There is no agreement on the key criteria that should be met before return to sport 11 21–23…”
Section: Introductionmentioning
confidence: 99%
“…3 However, hop and isokinetic tests do not consistently predict successful outcomes following ACL rehabilitation. Losciale et al 4 reported no associations between the use of RTS discharge tests and greater risk of reinjury, stating the low quality of evidence affects our ability to make definitive conclusions. Toole et al 5 reported that many young athletes had been cleared to RTS by their surgeon and rehabilitation specialist but failed to pass the RTS cut-offs cited in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13,25 The battery of hop tests used within the present study have demonstrated good discriminative accuracy and predictive abilities 7,24,32 ; however, the clinical utility of these and other commonly utilized return-to-sports assessment methods have recently been questioned due to a lack of association with secondary ACL injury risk. 26,27,34,42 In addition, several reports have identified that many athletes cleared to return to sports after ACLR are unable to achieve the contemporary standard of ≥90% LSI, 11,14,27,39 further challenging the clinical utility of these measures and raising concerns about the validity of the 90% LSI criteria to which post-ACLR athletes are held.…”
Section: Discussionmentioning
confidence: 99%